1991
DOI: 10.1093/geronj/46.1.m1
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes of Sympathetic Outflow to Muscles in Humans

Abstract: Muscle sympathetic nerve activity (MSA) was recorded microneurographically from the tibial nerve in 40 healthy male subjects aged 18 to 75. Passive and graded head-up tiltings were loaded on the subjects. The effects of aging on the resting activity of muscle sympathetic nerve in supine position at rest (burst number per minute), increase in MSA from the resting level by orthostasis (slope of the regression line between sine of the tilt angle and MSA bursts per minute), and the MSA in upright standing position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(68 citation statements)
references
References 0 publications
6
61
0
1
Order By: Relevance
“…To this end, the present investigation examined sympathetic nervous system activation in healthy young and older adults using a standardized whole body skin surface cooling protocol via water-perfused suit (3,30,51,55). Consistent with a wide body of literature examining MSNA at rest in older adults at thermoneutrality (27,39,53), older adults in the present study exhibited increases in basal muscle sympathetic outflow. Furthermore, whole body cold stress elicited pronounced increases in MSNA burst frequency and strength in older, but not young, adults.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…To this end, the present investigation examined sympathetic nervous system activation in healthy young and older adults using a standardized whole body skin surface cooling protocol via water-perfused suit (3,30,51,55). Consistent with a wide body of literature examining MSNA at rest in older adults at thermoneutrality (27,39,53), older adults in the present study exhibited increases in basal muscle sympathetic outflow. Furthermore, whole body cold stress elicited pronounced increases in MSNA burst frequency and strength in older, but not young, adults.…”
Section: Discussionsupporting
confidence: 60%
“…MSNA and plasma norepinephrine concentrations are elevated with advancing age (15,24,27,39,53); therefore, impairments in norepinephrine-mediated vasoconstriction have generally been attributed to sustained agonist-mediated desensitization in ␣-adrenergic receptor responsiveness (24). Conversely, the age-related increase in MSNA during cooling may be a compensatory response as a result of age-associated reductions in ␣-adrenergic receptor responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…46 As the increase in peripheral resistance upon standing is mediated by the sympathetic nervous system, 22 it seems that in elderly subjects the sympathetic activation is larger than in young subjects. However, the increase in microneurographically recorded muscle sympathetic nerve activity induced by orthostatic stress was much smaller in elderly subjects than in young subjects, 44 but the increase in circulating catecholamines upon standing was larger in elderly than young subjects. 47 -48 Thus, catecholamines and total peripheral resistance upon standing suggest an increase in sympathetic activity in the elderly.…”
Section: Spectral Analysismentioning
confidence: 78%
“…44 - 45 The evidence concerning the increase in sympathetic nerve activity during orthostatic stress is conflicting. In an earlier study we found that in the same subjects after 10 minutes of standing, compared with by guest on May 12, 2018 http://hyper.ahajournals.org/ Downloaded from being supine, the increase in peripheral resistance was much larger in elderly than young subjects.…”
Section: Spectral Analysismentioning
confidence: 99%
“…The muscle blood flow represents only 15-20% of the resting cardiac output, but during maximal exercise increases to approximately 85% of total cardiac output. With aging, neural activity [60][61][62] and endothelin-1 concentration 63) increase, while endothelial function [64][65][66] , aortic distensibility 67) , and capillary number decrease 8-11) . Moreover, erythrocyte-mediated ATP release, which mediates vasodilation during conditions of erythrocyte deoxygenation, decreases with aging 68) .…”
Section: Loss Of Blood Flow Volume With Agingmentioning
confidence: 99%